BMI-mediated association between glyphosate exposure and increased risk of atherosclerotic heart disease: A large-scale cross-sectional study - Wendi Xu; Zhe Chen; Yuhong Jiang; Hongbo Zeng; Nan He; Ziyi Liu; Meirong Zhou (PLoS ONE, 2025)
Background Glyphosate, as the main component of glyphosate pesticides, has been shown to have toxic effects on multiple human systems. However, the association between glyphosate and atherosclerotic cardiovascular disease (ASCVD) remains unclear. This study aims to explore the effect of glyphosate exposure on ASCVD. Methods This study involved 1,602 participants and employed various statistical techniques, such as multivariable logistic regression, linear fitting, mediation analysis, subgroup analysis, and sensitivity analysis, to elucidate the association between glyphosate exposure and cardiovascular diseases. Results Compared with the low level of glyphosate exposure, the risk of ASCVD increased significantly with high level of glyphosate exposure (OR = 2.05, 95%CI = 1.17–3.58, p<0.05, p for trend<0.05), which showed a linear upward trend. Further analysis found that exposure to high levels of glyphosate and angina pectoris (OR = 2.84, 95%CI = 1.00–8.04, p<0.05, p for trend<0.05), coronary heart disease (OR = 3.76, 95%CI = 1.80–7.83, p<0.01, p for trend<0.05), heart attack (OR = 2.65, 95%CI = 1.35–5.23, p<0.01, p for trend = 0.09) were associated. Mediating analysis found that BMI mediated the association between glyphosate exposure and ASCVD, with an indirect effect of 0.002405(95%CI: 0.000182–0.01, p = 0.02) and a direct effect of 0.039336(95%CI: 0.000391–0.09), total effect of 0.041741(95%CI: 0.002112–0.10). Conclusion Increased exposure to glyphosate is associated with an increased risk of ASCVD, and BMI plays a mediating role in this association. In addition, glyphosate exposure is associated with a higher risk of angina, coronary heart disease, and heart attack.